WEB-BASED TRANSACTION SYSTEM DESIGN FOR MAJULAPAN WORKSHOP SERVICES USING EXTREME PROGRAMMING METHOD - Muiz Ibrahim Samsul; Martantoh Eko (LPPM Unbaja, 2025)
In line with the advancement of information technology, Bengkel Majulapan has started to adopt web-based applications to enhance operational efficiency and service quality. Previously, the service booking process, spare part management, and technician scheduling were carried out manually, often resulting in errors and a lack of transparency. To overcome these problems, this study designs a web-based transaction system using the Extreme Programming (XP) method. XP was chosen for its fast development cycle and flexibility to adapt to changes. The system is built using web technologies such as HTML, CSS, and JavaScript for the frontend, with Firebase used for authentication, real-time database, and notification features. The application allows users to book services, manage spare parts, and receive notifications, which can be accessed anytime and anywhere. This system aims to improve the transparency, accuracy, and efficiency of transaction processes within the workshop. The development stages include planning, designing user stories, system development, testing, and deployment. The results showed that the implementation of the system increased booking accuracy, reduced manual errors, and improved customer satisfaction based on feedback and trial use. With this system in place, it is expected that Majulapan Workshop's operational performance becomes more efficient and effective.